Development Trends of E-Modules in Science Education for Fostering 21st-Century Skills: A Narrative Review - Gunawan Gunawan; Lovy Herayanti; Muhammad Hilmy As Shiddiq (Indonesian Publication Center, 2026)
The post-pandemic integration of technology in education has accelerated the transformation of teaching materials from print to digital formats. This study aims to provide a narrative review of current trends in the development of electronic modules (E-Modules) in science education, specifically focusing on fostering 21st-century skills. By analyzing recent literature (2021–2025), this review identifies a shift from mere content digitalization to the creation of complex interactive media. Key findings indicate that: (1) Current E-Module development is dominated by the integration of active pedagogical models, particularly Problem-Based Learning (PBL) and STEM (Science, Technology, Engineering, and Mathematics) approaches; (2) There is a distinctive trend of merging digital technology with local wisdom (Ethnoscience) to enhance learning relevance; and (3) The primary learning outcomes targeted are critical thinking, science literacy, and problem-solving skills. This review concludes that modern E-Modules no longer function solely as passive reading resources but as interactive learning environments that effectively bridge scientific conceptual understanding with future competency demands.